2012
DOI: 10.1002/ccd.24498
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcomes of consecutive patients treated by endeavor zotarolimus and resolute zotarolimus stents: The impact of polymer coating in drug‐eluting stent technology

Abstract: The results of this study suggest that the clinical outcome of patients treated by DES differing for the polymer coating only may be different. Polymer coating is a pivotal, probably underrated, component of DES technology which may influence the clinical performance of DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…7,8 This study was approved by the institutional review board, and written informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 This study was approved by the institutional review board, and written informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Second‐generation DES, including everolimus‐ and zotarolimus‐eluting stents, have been developed with improved stent polymer biocompatibility that reduce local inflammatory responses . However, inconsistent rates of ISR are still reported despite the growing use of second‐generation DES suggesting an involvement of other mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…In the RESOLUTE All-Comers trial, the rate of definite ST was significantly higher in the R-ZES group (1.2%) than in the XV-EES group (0.3%, P = 0.01) at 12 months, which was primarily related to a higher rate of definite ST at 30 days in the zotarolimus-stent group than in the everolimus-stent group. 23 Talarico et al, 28 reported a significantly higher number of definite, probable, and possible cases of ST in the E-ZES group (with one case of definite ST), while no definite or probable …”
Section: In-stent Thrombosismentioning
confidence: 96%
“…Lesion complexity is another factor that was described in some studies, 8,20,22,23,25 including the one by Talarico et al 28 that described that patients treated with the R-ZES had longer and more complex lesions, with higher rate of ACC/AHA B2/C, 30 and higher SYNTAX™ score 40,41 and bifurcated lesions. The outcome in bifurcation lesions was evaluated in the multicenter Italian registry that evaluated lesions with more than 70% stenosis at a major bifurcation point and a main vessel diameter of more than 2.5 mm.…”
Section: Lesion Length and Complexitymentioning
confidence: 96%
See 1 more Smart Citation